The role of 68Ga-FAPI PET/CT for patients with malignancies of the lower gastrointestinal tract: first clinical experience - Körber, Stefan A.; Kratochwil, Clemens; Adeberg, Sebastian; Ungerechts, Guy; Rathke, Hendrik; Winter, Erik; Lindner, Thomas; Syed, Mustafa; Bhatti, Irfan A.; Herfarth, Klaus; Jäger, Dirk; Haberkorn, Uwe; et al. (Journal of nuclear medicine, 2020)
For oncologic management or radiotherapy planning, reliable staging tools are essential. The recent development of quinoline-based ligands targeting cancer-associated fibroblasts demonstrated promising preclinical and clinical results. The current study aimed to evaluate the role of fibroblast activation protein inhibitor (FAPI) PET/CT as a first clinical analysis for primary malignancies within the lower gastrointestinal tract (LGT). Methods: 68Ga-FAPI PET/CT was performed on a cohort of 22 patients with LGT tumors, including 15 patients with metastatic disease, 1 patient with suspected local relapse, and 6 treatment-naïve patients. Uptake of 68Ga-FAPI-04 and 68Ga-FAPI-46 was quantified by SUVmax and SUVmean. After comparison with standard imaging, changes in tumor stage or localization and in oncologic or radiooncologic management were recorded. Results: The highest uptake of FAPI tracer was observed in liver metastases and anal cancer, with an SUVmax of 9.1 and 13.9, respectively. Because of low background activity in normal tissue, there was a high tumor-to-background ratio of more than 3 in most lesions. In treatment-naïve patients, TNM was changed in 50%, whereas in patients with metastases, new findings occurred in 47%. In total, FAPI imaging caused a high, medium, and low change in oncologic or radiooncologic management in 19%, 33%, and 29%, respectively. For almost every patient undergoing irradiation, target volume delineation was improved by 68Ga-FAPI PET/CT. Conclusion: The present study demonstrated that both primary and metastatic LGT tumors were reliably detected by 68Ga-FAPI PET/CT, leading to relevant changes in TNM status and oncologic or radiooncologic management. 68Ga-FAPI PET/CT seems to be a highly promising imaging agent for the diagnosis and management of LGT tumors, potentially opening new applications for tumor staging or restaging.